Challenges of cancer control in developing countries: current status and future perspective. (October 2011) - Sharma, Vanita; Kerr, Stewart H; Kawar, Zsana; Kerr, David J
Cancer is a global problem accounting for almost 13% of all deaths worldwide. This equates to over 7 million people a year, more than is caused by HIV/AIDS, TB and malaria combined. Now is the time to strengthen the health systems of developing countries to deal with cancer, to avoid a future crisis similar to the HIV/AIDS pandemic. In this article we discuss the current state of cancer in the developing world, how we need to advocate for a change in cancer control policy with the governments of developing nations/transnational governmental bodies (e.g., the UN and WHO etc) and how we think cancer care could be improved in developing countries. We feel the only way to overcome the growing burden of cancer in the developing world is working in partnership with, nongovernmental organizations, international nongovernmental organizations, transnational governmental bodies and governmental bodies.